2021
DOI: 10.1073/pnas.2022586118
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of the D614G substitution on the structure of the spike glycoprotein of SARS-CoV-2

Abstract: The majority of currently circulating severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) viruses have mutant spike glycoproteins that contain the D614G substitution. Several studies have suggested that spikes with this substitution are associated with higher virus infectivity. We use cryo-electron microscopy to compare G614 and D614 spikes and show that the G614 mutant spike adopts a range of more open conformations that may facilitate binding to the SARS-CoV-2 receptor, ACE2, and the subsequent stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
179
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(201 citation statements)
references
References 31 publications
(47 reference statements)
20
179
0
2
Order By: Relevance
“…These various mutations may provide an avenue for the SARS-CoV-2 to escape from immunity of the current vaccine against COVID19. Because of this, recent SARS-CoV-2 variant B.1.351, particularly those with mutations in the RBM of spike that potentially bring about conformational changes to the spike protein, got attention [1,17,19]. Herein, we show that K417N and E484K spike mutations derived from SARS-CoV-2 B.1.351 variant has a greater affinity for ACE2 as compared to the D614G derived from SARS-CoV-2 Wuhan variant via MD simulation-based predictions (Table 1 and Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…These various mutations may provide an avenue for the SARS-CoV-2 to escape from immunity of the current vaccine against COVID19. Because of this, recent SARS-CoV-2 variant B.1.351, particularly those with mutations in the RBM of spike that potentially bring about conformational changes to the spike protein, got attention [1,17,19]. Herein, we show that K417N and E484K spike mutations derived from SARS-CoV-2 B.1.351 variant has a greater affinity for ACE2 as compared to the D614G derived from SARS-CoV-2 Wuhan variant via MD simulation-based predictions (Table 1 and Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…A similar behavior is seen with the wild-type sequence (D614), which has lower neutralization than G614 even if no other difference is present; a plausible explanation is that G614 makes the CoV-X2 epitopes more accessible by favoring the RBD ‘up’ conformation. 17 We conclude that the in vitro binding and neutralizing properties of CoV-X2 make it preferable over its parental antibodies.…”
mentioning
confidence: 86%
“…Several studies pointed to the hypothesis that this mutation confers enhanced transmissibility [ 23 ], and may increase infectivity by assembling more functional S protein into the virion [ 24 , 25 ]. The cryo-electron microscopy structure of the G614 S variant showed that it adopts a predominantly open conformation, likely promoting a more proficient binding to ACE2, whereas the D614 S is mostly closed [ 26 ]. This may account for virus’ observed augmented infectivity and its current predominance.…”
Section: Introductionmentioning
confidence: 99%